Orphanet Journal of Rare Diseases - Palau, Francesc
Orphanet Journal of Rare Diseases is an open access, peer-reviewed journal that encompasses all aspects of rare diseases and orphan drugs. The journal publishes high-quality reviews on specific rare diseases. In addition, the journal may consider articles on clinical trial outcome reports, either positive or negative, and articles on public health issues in the field of rare diseases and orphan drugs.